Assessment of Nutritional Status among Adult Hemophilia Patients in Gaza Strip - Ibrahim M. Ashour (Proceedings, 2023)
Congenital Hemophilia is an X-linked bleeding disorder caused by a deficiency of coagulation factor VII (in hemophilia A) or factor IX (in hemophilia B). The deficiency is the result of mutations of respective clotting factor genes. In the Gaza strip, 124 cases of hemophilia were observed. The main treatment for those patients is replacement of the missing factors along with supportive measures. To our knowledge, no studies were conducted in the Gaza Strip concerning nutritional status in hemophilic patients. A descriptive study that utilized a questionnaire to assess nutritional status among 27 adult male hemophilic patients managed at the Hemophilia and Thalassemia Clinic in the European Gaza Hospital from March to April 2019 was conducted. All the patients fully answered the questionnaires that included sociodemographic, socioeconomic, medical, nutritional and anthropometric characteristics. The diet diversity score for all the participants patients using mean (SD) was the following: Starches, 9.8 (0.769); Beverages, 9.6 (1.000); Vegetables, 7.8 (1.545); Fruits, 6.7 (2.215); Snacks, 6.3 (3.667); Legumes, 6.8 (1.459); Poultry, 5.0 (0.337); Meat, 4.9 (1.154); Eggs, 4.7 (1.846); Grains, 4.5 (2.375); Dairy Products, 4.2 (2.991); Soups, 4.1 (2.100); Fish, 3.8 (2.088); Nuts, 3.7 (2.270); and Sweeteners, 3.4 (2.857). Notably, only 17 patients (63.0%) were aware of the current dietary reference intakes. Moreover, most participants acknowledged the importance of providing nutritional patient education. In addition to medical treatment, hemophilic patients need to improve their nutritional status. This can be achieved through education and increase in patient awareness.